Landslide Susceptibility Analysis Based on Geographic Information System in Ambon City - Yamco, Yuliana; Leuwol, Ferdinand Salomo; Lasaiba, Mohammad Amin (Jurnal Pendidikan Geografi Unpatti, 2022)
Disaster is an event that threatens and disrupts people's lives and livelihoods. Landslide is one type of mass movement of soil or rock, or a mixture of both, down a slope due to disruption of soil stability. The cause of landslides apart from human activity is also due to natural factors, namely rain. There are two things that cause landslides related to rain, namely high-intensity rain in a short time and hitting areas with unstable soil conditions. Geographic information system (GIS) also provides spatial data, which can be used for landslide hazard inventory and zoning maps, Geographic Information System used in this study because it is proven to be able to provide geospatial data information for each object on the earth's surface quickly, as well as provide a spatial analysis system that so that mitigation efforts can be carried out aimed at preventing hazards (risks) from becoming disasters or reducing the effects that occur when the disaster hasoccurred Ambon City based on its physiography, most of its areas are hilly to mountainous areas, about 89% with slope conditions up to steep and only about 11% in the form of plains.